The Safety and Efficacy Results of Tenecteplase in Patients with ST Segment Elevation Myocardial Infarction in a Center with No Possibility of Coronary Intervention (Annals of Medical Research, 2021)
None
Keywords: Tenectaplase; Drug Security; Efficacy